Гостре ураження нирок при запальних процесах і шляхи їх корекції = Acute kidney damage in inflammatory processes and ways of their correction - Sirman, V. M.; Borys, R. M.; Nykytenko, O. P.; Zukow, W.; Gozhenko, A. I. (Journal of Education, Health and Sport, 2016)
Sirman V. M., Boris R. M., Nykytenko O. P., Zhukow W., Gozhenko A. I. Гостре ураження нирок при запальних процесах і шляхи їх корекції = Acute kidney damage in inflammatory processes and ways of their correction. Journal of Education, Health and Sport. 2016;6(7):11-26. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56841 http://ojs.ukw.edu.pl/index.php/johs/article/view/3653 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 28.06.2016. Гостре ураження нирок при запальних процесах і шляхи їх корекції В. М. Сірман, Р. М. Борис, О. П. Никитенко, В. Жуков, А. І. Гоженко Державне підприємство «Український науково-дослідний інститут медицини транспорту МОЗ України», м. Одеса, Украина Резюме Метою дослідження було вивчення функціонального стану та механізмів порушеннями нирок при експериментальному перитоніті, а також при ад’ювантному артриті Пірсона у щурів. Для вирішення поставлених задач проведені серії експериментів in vivo. У роботі використано 189 самців білих щурів з середньою масою тіла 0,193±0,018 кг. Дослідження проводили через 2, 4, 6 і 12 міс. після індукції ад’ювантного артриту Пірсона. При експериментальному перитоніті, проведено 7 серій експериментів на 486 самцях білих щурів з масою тіла 0,17-0,30 кг. Встановлено, що при обох експериментальних моделях запалення виникають однотипні порушення функції нирок, які виявляються у зменшенні діурезу, зростанні екскреції білка та натрію, що пов’язано як із падінням швидкості клубочкової фільтрації, так і канальцевої реабсорбції води та натрію. Їх розвиток відрізняється у часі та залежить від строків виникнення та динаміки запального процесу. Ключові слова: гостре ураження нирок, ХХН, ХНН, ШКФ. Acute kidney damage in inflammatory processes and ways of their correction V. M. Sirman, R. M. Boris, O. P. Nykytenko, W. Zhukow, A. I. Gozhenko SE "Ukrainian Scientific Research Institute of Transport Medicine, Ministry of Health of Ukraine Resume The aim of the study was to investigate functional status and mechanisms of disorders of the kidneys in experimental peritonitis, as well as adjuvant arthritis in rats Pearson. To solve this problem, a series of experiments in vivo. The paper used 189 male albino rats with an average body weight of 0,193 ± 0,018 kg. The study was conducted at 2, 4, 6 and 12 months. After induction of adjuvant arthritis Pearson. In experimental peritonitis, 7 held a series of experiments on 486 white male rats weighing 0,17-0,30 kg. Found that in both experimental models of inflammation arising same type of renal dysfunction, which are to reduce urine output, increasing excretion of sodium and protein, which is associated with a drop in glomerular filtration rate and tubular reabsorption of water and sodium. Their development is different in time and depends on the timing of the emergence and dynamics of inflammation. Keywords: acute kidney damage, CKD, chronic renal failure, GFR.